Structural and Raman spectroscopic characterization of pyroxene‐type compounds in the CaCu1−xZnxGe2O6 solid‐solution series. Issue 3 (1st June 2017) - Redhammer, Günther J.; Tippelt, Gerold; Reyer, Andreas; Gratzl, Reinhard; Hiederer, Andreas
Abstract : The clinopyroxene CaCuGe2 O6 transforms from P 21 / c ↔ C 2/ c with increasing replacement of Cu 2+ by Zn 2+ . The structural phase change is characterized using single‐crystal X‐ray diffraction and temperature‐dependent Raman spectroscopy. Abstract : Pyroxene‐type germanate compounds with the composition CaCuGe2 O6 –CaZnGe2 O6 have been synthesized via a solid‐state ceramic sintering route. Phase‐pure polycrystalline and small single‐crystal material was obtained all over the series, representing a complete solid‐solution series. Differential thermal analysis, single‐crystal X‐ray diffraction and Raman spectroscopy were used to characterize phase stability, phase changes and structural alterations induced by the substitution of Cu 2+ with Zn 2+ . Whereas pure CaCuGe2 O6 exhibits P 21 / c symmetry with a strong distortion of the M 1 octahedra and two different Ge sites, one of them with an unusual fivefold coordination, the replacement of Cu 2+ by Zn 2+ induces a chemically driven phase change to the C 2/ c symmetry. The phase change takes place around Zn 2+ contents of 0.12 formula units and is associated with large changes in the unit‐cell parameters. Here, the increase of c by as much as 3.2% is remarkable and it is mainly controlled by an expansion of the tetrahedral chains. Further differences between the P 21 / c and C 2/ c structures are a more regular chain of edge‐sharing M 1 octahedra as a consequence of more and more reduced Jahn–Teller distortion and a less kinked, symmetry‐equivalent tetrahedral chain. The coordination of the Ca site increases from sevenfold to eightfold with large changes in the Ca—O bond lengths during the phase change. Raman spectroscopy was mainly used to monitor the P 21 / c to C 2/ c phase change as a function of composition, but also as a function of temperature and to follow changes in specific Raman modes throughout the solid‐solution series.